MOSLEM BEHAVIOR TOWARD DEBT MANAGEMENT - Lestari, Wiwik; Silvy, Meliza (International Journal of Islamic Business & Management, 2022)
Islam teaches Muslims to be clever in seeking of “rizki” (income) and spending it wisely to achieve well-being, happiness in the Islamic way. This study aims to prove whether Islamic Financial Knowledge, religiosity, self-control, and lifestyle are determinants of debt management behavior in Muslim communities. Furthermore, this study also examines whether debt management behavior affects financial well-being. This study is a quantitative study using a carefully developed questionnaire and tested for validity and reliability. The selected samples are residents of Surabaya who earning money from work.  By surveying 331 respondents and using SEM analysis tools, behavior towards debt was confirmed as a determinant of welfare even the correlation number is small but significant. This study also proved that financial knowledge does not affect self-control but lifestyle and religiosity do. Furthermore, financial knowledge together with self-control and religiosity are predictor of behavior. Interestingly, the result shows that the higher the religiosity, the lower the debt behavior. This fact may be since there are some cultural rituals on a religious event that need extra spending. This result implies that Moslem should be careful with their lifestyle especially regarding Islamic events and consumerism as identity since it can reduce self-control and in turn potentially lower financial management. Using debt to fulfill the lifestyle is dangerous for well being.JEL Classification Codes: D1, I22, R11.